Four channel optical demultiplexer based on L2 photonic crystal microcavity - Ammari, Merzoug; Benmerkhi, Ahlem; Bouchemat, Mohamed (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
The wavelength demultiplexing is a particularly important function in integrated optics and can be realized using photonic crystals. The aim is to extract accurately the wavelengths in a data flux. In this work, we investigate a new topologies of wavelength demultiplexing based on two-dimensional photonic crystals constituted of dielectric rods spread in a square network. The studied demultiplexer is based on optical filters with optimized parameters in order to extract four different wavelengths in the vicinity of frequencies corresponding to communication windows. It was found that the crosstalk between the structure channels of the demultiplexer are in the range of –19.19 and –44.1 dB and the channel spacing is equal to 0.96 nm. The simulation results presented in this paper are performed and analyzed using the FDTD method.
Optica Applicata, Vol. 52, 2022, nr 4, s. 613-625
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; photonic crystal; cavity; waveguide; quality factor; demultiplexer; FDTD; filter; crosstalk